Sirt2 functions in spindle organization and chromosome alignment in mouse oocyte meiosis - Zhang, Liang (Federation of American Societies for Experimental Biology, 2014)
Sirtuins have been widely reported to be involved in multiple biological processes; however, their function in oocyte meiosis has not been. Here, by confocal scanning and quantitative analysis, we show that specific depletion of Sirt2 in mouse oocytes results in spindle defects and chromosome disorganization (35.5±8.7 vs. 9.6±3.8% control; P<0.05), with impaired microtubule-kinetochore interaction. Moreover, knockdown and overexpression experiments reveal that Sirt2 modulates the acetylation status of histone H4K16 and α-tubulin in oocytes, which may in part mediate the defective phenotypes described above by influencing microtubule dynamics and kinetochore function. Finally, we find lower Sirt2 protein level in oocytes from aged mice by immunoblotting and that maternal age-associated meiotic defects can be ameliorated through overexpression of Sirt2 (33.2±5.1% old vs.12.7±5.2% old+Sirt2; P<0.05), providing support for the hypothesis that decreased Sirt2 is one of a number of factors contributing to oocyte age-dependent deficits. In summary, our data indicate a role for Sirt2 during oocyte meiosis and uncover a striking beneficial effect of increased Sirt2 expression on aged oocytes.—Zhang, L., Hou, X., Ma, R., Moley, K., Schedl, T., Wang, Q. Sirt2 functions in spindle organization and chromosome alignment in mouse oocyte meiosis.